An Analysis of Teacher and Student Conversation in EFL Classroom Interaction by Using Foreign Language Interaction Analysis System in Class XI at SMK Negeri 1 Singaraja Academic Year 2017/2018 - A.N.P. Dewi (Universitas Pendidikan Ganesha, 2018)
This study aimed at 1) find out classroom interaction categories by using FLINT that exist during English teaching learning process in class XI at SMK N 1 Singaraja using FLINT system. 2) Identifying categories of classroom interaction by using FLINT which are the most and least frequently occurs during the teaching-learning process in class XI at SMK Negeri1 Singaraja 3) discovering the reasons of the interaction during the teaching-learning process in class XI at SMK Negeri 1 Singaraja. This research was a descriptive study by using qualitative approach. There was one class as a sample for this research. The data were collected based on the instruments such as research observation, interview guide, video camera and note-taking . The results of the study show that, 1) two categories of foreign language interaction (FLINT) analysis system all categories of FLINT are occurred during learning process in XI B in SMK N 1 Singaraja, 2) The most frequently occurred of interaction category during three times observation was ‘ask question’ category.it appeared 121 times in the first meeting, 72 times in the second meeting, and 60 times in the third meeting. The total frequency of asking question was 253 or 24,5% 3) the reason of the occurrence of ‘ask question’ category is the difficulty of the students in learning and the students need teacher’s guidance.